Професор Світлана Яківна Єрмоленко - Бибик, С.П. (Мовознавство, 2017)
У статті висвітлено життєвий і творчий шлях С.Я. Єрмоленко, окреслено її внесок у розвиток українського мовознавства — лінгвостилістики, лінгвофольклористики, історії літературної мови, лексикографії, лінгводидактики та культури мови, відзначено роль дослідниці в популяризації концептуально-знакового наповнення текстів української літературної та народнопісенної практики. The article highlights the life and career of the famous Ukrainian scientist, outlined the contribution of the scientist to the development of Ukrainian linguistics — of the linguistic stylistics, folklore language, history of the literary language, lexicography and lingvodedactic methods of language learning and culture of speech. The article noted the role of the researcher in promoting conceptual and symbolic content of the texts of the Ukrainian literary language and folk songs.